Carbapenem-resistant Enterobacteriaceae dispersal from sinks is linked to drain position and drainage rates in a laboratory model system. Issue 1 (May 2019) - ,; Aiken, Zoie; Akinremi, Oluwafemi; Ali, Aiysha; Cawthorne, Julie; Cleary, Paul; Crook, Derrick W.; Decraene, Valerie; Dodgson, Andrew; Doumith, Michel; Ellington, Matthew; Eyre, David W.; et al.
Summary: Background: Hospital sinks, waste traps and drains can harbour carbapenem-resistant Enterobacteriaceae (CRE). Aim: To investigate the dispersal of CRE from sinks in which water delivered from the tap flows directly into the drain and from clinical handwash basins with the drain at the rear. The effect of fast and slow drainage rates was also assessed. Methods: Waste traps, known to be colonized with CRE, were taken from a hospital and installed within a model laboratory system. New waste traps were also installed and artificially inoculated with CRE. The potential for bacteria to be dispersed from sinks was assessed using cyclone air samplers and/or settle plates. Findings: When the waste traps were artificially contaminated and CRE colonization was confined to the waste trap water, significantly fewer bacteria were dispersed from sinks that drained quickly ( P  = 0.004) and/or from rear-draining sinks ( P  = 0.002). When the waste traps were naturally contaminated and CRE colonized the trap, pipework and drain, there was significant interaction between sink drainage and position of the drain ( P  < 0.001). When drainage was slow, dispersal from rear-draining sinks was almost 30-fold less than from sinks with the drain underneath the tap ( P  < 0.001). When drainage was fast, rear-draining sinks again released comparatively fewer CRE, although, in this case, the difference was not statistically significant ( P  = 0.7). Contaminated splashes travelled up to 1 m from the sink. Conclusion: Slow drainage rates and sink designs with the drain directly underneath the tap increase the risk of CRE present in waste traps and drains contaminating the ward environment.